Oral giant cell tumor or giant cell granuloma: How to know? - E. Hoarau; P. Quilhot; V. Baaroun; G. Lescaille; F. Campana; R. Lan; J. Rochefort (Heliyon, 2023)
Introduction: The distinction between giant cell tumors and giant cell granulomas is challenging, as both entities have overlapping diagnostic criteria, especially in oral locations. The two entities have similar clinical and radiological presentations, but they differ in their prognoses. Objective: The main objective of this study was to list the clinical, radiological, histological, and prognostic features of maxillomandibular giant cell tumors and giant cell granulomas cases n order to assess their value as a diagnostic referral factor that may allow the distinction between maxillo-mandibular giant cell granuloma and giant cell tumor. Study design: Data of maxillomandibular giant cell granulomas and giant cell tumors were assessed through a scoping review and a pre-existing systematic review of literature. We have also realized a bicentric retrospective study. Results: Various criteria facilitate the differential diagnosis like age, size, locularity and presence of necrosis zone but not the gender. The most discriminating factors was symptomatology (reported in 72% of GCTs while only 15% of GCGs) and the distribution pattern of giant cells in the stroma (homogeneously dispersed in 80% of GCTs versus grouped in clusters in 86.7% of GCGs). Recurrences were most described for giant cell tumors than giant cell granulomas. Malignant transformation and pulmonary metastasis were exclusively reported for giant cell tumors. Conclusion: As clinical and radiological elements are not sufficient to distinguish between these two entities, immunohistochemistry and molecular genetics can be represent diagnostic biomarkers to distinguish giant cell granulomas and giant cell tumors in oral cavity. We have attempted to define the main criteria for the differentiation of giant cell tumor and giant cell granuloma and propose a decision tree for the management of single maxillomandibular giant cell lesions.